SEMANTIC ANALYSIS OF FRAUDULENT ADS IN FACEBOOK - Rais, Burhanudin; Widodo, Pratomo (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2019)
This study aims to analyse the semantic features in fraudulent ads in Facebook. This study is conducted by using two kinds of advertisement which are found in Facebook. The researchers are analyzing the word, sentence, or phrase that suspected as the way to convince the customers by following theory of meaning from Leech (1981). The data that the researchers got showed that the first type of advertisement is emphasized more to the affective and social meaning where the seller leads the customers’ opinion that the seller is a good or trusted person. Moreover, the seller uses prase that include to conceptual meaning to explain the condition or specification of the cellphone in detail.In the second type of advertisement, the element emphasized by the seller is thematic mining by referring to the emphasis of the word used in the advertisement.More over, theresult for identification of fraudulent ads in this study is still dominated by the usual way, such as by looking at the price offered. However, the results of this study can also be used as a consideration in identifying fraudulent ads.